"Beyond the Surface": Hermeneutic Implications of Blue by MOPDTK. (2nd January 2018) - Gabric, Lukas
ABSTRACT: The 2014 album Blue by the group MOPDTK (Mostly Other People do the Killing) is an exact, musical one-to-one reproduction of Miles Davis's iconic and best-selling recording Kind of Blue (1959). In this project, I argue that while Blue sounds and appears as jazz, it is much rather a conceptual idea borrowed from a literary example, in the disguise of Jazz. Blue raises questions that are central to the understanding of the mens auctoris, genre, and art in general. In regard to the mens auctoris, the question mainly pertains to intent and originality. In the scope of art in general, we are faced with the question about the relationship between replication and value (monetary and artistic). Blue also evoked typical reactions associated with a work that questions assumptions about genre. Upon its initial reception, many listeners seemed unable to place it confidently and categorize the album according to genre.